Integration of rehabilitation and palliation for people with severe lung disease or heart failure – a scoping review - Kristoffer Marsaa; Stig Molsted; Christian Have Dall; Henrik Hansen; Lise Nottelmann; Jette Meelby; Thomas A. Schmidt; Laura Hohwü Thomsen; Nina Godtfredsen (European Clinical Respiratory Journal)
Traditionally, rehabilitation and palliative care are delivered as separate services, where rehabilitation focuses on regaining physical functions and palliative care on symptom relief and existential support. There is growing recognition of the potential benefit in integrating these approaches. This scoping review explores how integration or coordination of rehabilitation and palliative care is described in the literature, with a focus on heart failure, chronic obstructive pulmonary disease, and interstitial lung disease. A systematic search was conducted in MEDLINE, EMBASE, and CINAHL, identifying 20 relevant publications. Six overarching themes emerged: overlapping treatment goals; timing of services; inclusion of advance care planning (ACP); attention to existential and spiritual dimensions; barriers to integration; and the role of informal caregivers. The majority of the included studies were re-views or expert statements, with few interventional studies. Practical implementation remains limited and poorly defined. While guidelines increasingly support integrated care models, significant challenges persist, including lack of conceptual clarity, limited evidence of effect, and unclear roles for caregivers. There is broad consensus that integration could improve quality of life for both patients and caregivers by combining the functional focus of rehabilitation with palliative symptom management and its holistic approach. While publications support this integration, its implementation in clinical practice remains unclear. A key argument for integration is the overlap in treatment goals and the potential synergy between the two approaches. Several studies highlight the opportunity to incorporate end-of-life discussions, such as ACP, into traditional rehabilitation programs. Introducing palliative care principles earlier in rehabilitation may also increase the number of patients receiving appropriate end-of-life care.